2018
DOI: 10.1055/s-0038-1667349
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Risk and the Mucopolysaccharidoses: A Challenging and Changing Landscape

Abstract: The mucopolysaccharidoses (MPS) are well known to present a high risk of anesthesia. Predominantly, this risk is not only related to upper airway issues but also to multilevel airway obstruction, respiratory morbidity, and cardiac issues. Before disease-specific treatment became available, the management of the untreated patients with MPS was regarded as the worst airway problem in pediatric anesthetic practice. The last 20 to 30 years have seen great advances in the treatment of the different types of MPS wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Besides that, these patients can also have a higher-positioned epiglottis and limited mouth opening secondary to temporomandibular joint dysplasia and micrognathia [15]. Some patients, especially those with MPS IVA [8], can also have tortuous and narrowed tracheas and tracheomalacia [3,5,7,[14][15][16][17]. Based on this evidence, a computed tomography scan of the airway with the creation of three-dimensional reconstructions of the trachea and flexible endoscopy is desirable in these patients [3,5,7,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides that, these patients can also have a higher-positioned epiglottis and limited mouth opening secondary to temporomandibular joint dysplasia and micrognathia [15]. Some patients, especially those with MPS IVA [8], can also have tortuous and narrowed tracheas and tracheomalacia [3,5,7,[14][15][16][17]. Based on this evidence, a computed tomography scan of the airway with the creation of three-dimensional reconstructions of the trachea and flexible endoscopy is desirable in these patients [3,5,7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients, especially those with MPS IVA [8], can also have tortuous and narrowed tracheas and tracheomalacia [3,5,7,[14][15][16][17]. Based on this evidence, a computed tomography scan of the airway with the creation of three-dimensional reconstructions of the trachea and flexible endoscopy is desirable in these patients [3,5,7,14,15]. Skeletal dysplasia such as atlantoaxial instability, spinal cord compression mainly at the craniocervical and thoracolumbar regions, limited neck mobility, pectus carinatum, and scoliosis are features frequently found in these patients which can potentiate a difficult airway [3,5,7,10,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2018, Walker et al [139] reported a 14% incidence rate of airway complications patients with MPS I treated with HSCT, compared with 57% in patients with MPS I treated with ERT. Frawley et al [140] reported similar post-HSCT findings in a smaller group of patients with MPS IH.…”
Section: Hsct For Each Type Of Mps Mps Imentioning
confidence: 99%